2000
DOI: 10.1093/jn/130.9.2312
|View full text |Cite
|
Sign up to set email alerts
|

A High-Protein Meal Exceeds Anabolic and Catabolic Capacities in Rats Adapted to a Normal Protein Diet

Abstract: The postprandial fixation of dietary nitrogen in splanchnic and peripheral tissues as well as its dynamic transfer to the nitrogen pools of the body were quantified in rats subjected to an acute augmentation of dietary protein. For this purpose, we traced the dietary protein and studied the immediate fate of exogenous nitrogen in many tissues and biological fluids. Rats were adapted to a diet providing an adequate protein level (14 g/100 g), and then fed a meal containing either 0.42 g (Group A) or 1.50 g (Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
8
33
0
Order By: Relevance
“…Our observations support the idea of the important role of gastric empting rate on the regulation of amino acid utilization in the rat. The deceleration of gastric empting in response to the saturation of catabolic capacities by a meal high in protein was previously reported by Morens et al (2000). Türker and Yildirim (2011) showed that because of slower digestion, a six-meal feeding strategy was more efficient in terms of weight gain compared with 2, 3, or 4 meals.…”
Section: Discussionsupporting
confidence: 64%
“…Our observations support the idea of the important role of gastric empting rate on the regulation of amino acid utilization in the rat. The deceleration of gastric empting in response to the saturation of catabolic capacities by a meal high in protein was previously reported by Morens et al (2000). Türker and Yildirim (2011) showed that because of slower digestion, a six-meal feeding strategy was more efficient in terms of weight gain compared with 2, 3, or 4 meals.…”
Section: Discussionsupporting
confidence: 64%
“…During prolonged fasting, the breakdown of skeletal muscle generates limited carbon resources in the form of AAs such as alanine. Hence, both fasting and feeding of a high-protein diet (HPD) can stimulate AA deamination and urea production in the liver (13), where AA carbon skeletons are converted into glucose or lipids. For most AAs, the amino group is transferred to α-KG to generate glutamate and other α-keto acids.…”
mentioning
confidence: 99%
“…Even with the higher protein supply in the high-protein-fat diet, no significant differences were observed in the serum and hepatic total protein, because all excess of protein which the body does not use for the synthesis of hormone, enzymes and plasma proteins or in gluconeogenesis or in maintaining muscle mass, is excreted by the body as urea [44], or is oxidized to provide energy, because there is no place in the body for permanent storage of protein [45]. Probably, the excess of protein from high-protein-fat diet were oxidized because there was an increase in protein carbonyl concentration in the liver of HPF group.…”
Section: Discussionmentioning
confidence: 98%